Nest climate and blood quality of two host species of the ectoparasitic Philornis downsi in the Galapagos Islands as factors of larval development - Pike, Courtney L.; Hood-Nowotny, Rebecca; Kofler, Barbara; Richner, Heinz; Tebbich, Sabine (Frontiers in Ecology and Evolution, 2024)
The avian vampire fly is an invasive species on the Galapagos Islands, where its hematophagous larvae utilize nestling birds as hosts. It poses a serious threat to populations and species of Darwin finches and other avian species. Prior studies suggest that the avian vampire fly larvae develop more rapidly in nests of small tree finches compared to sympatric green warbler finch nests. Here we investigate factors that may differentially influence larval growth in the two host species, including nest microclimate and nestling diet. We collected nest base temperature and humidity data as proxies for nest microclimate. As indicators of dietary composition and quality, we measured stable isotope δ13C and δ15N composition of nestling blood, used the C:N ratios as an indicator of relative protein content, and assessed the amino acid composition of the blood. The hematophagous larvae living off nestling blood were analyzed for the same parameters except amino acid composition. The effect of nest base humidity on nest base temperature significantly depended on bird species: at low humidity levels nest base temperature was higher in the small tree finch, and declined in both species as nest base humidity increased, which suggests higher stable heat capacity of small tree finch nests. The effect of age group based on the predicted onset of thermoregulation was marginally significant. Nest base temperatures were significantly higher in small tree finch nests during the predicted female brooding period before fully effective thermoregulation. Stable isotope δ13C levels were significantly higher in the blood of small tree finch nestlings compared to warbler finch nestlings, suggesting a difference in nestling food composition and source, while. δ15N levels were similar. The C:N ratios and amino acid composition of nestling blood were not significantly different between the two species, suggesting similar dietary quality. Thus, the faster development of larvae in small tree finch nests may be due to higher nest base temperatures during the early nestling phase rather than host blood quality parameters.